Development of electronic handouts for class X high school ecosystem materials for online learning - Jeklin Hutagaol; Ervan Johan Wicaksana; Jodion Siburian (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
Students' low interest is the most common problem in online learning. As a solution, we need media that is attractive and easy to use. This study aims to (1) develop electronic handouts on the Ecosystem topic for class 10th-grade senior high school for online learning, (2) determine the feasibility of handouts, (3) determine teacher perceptions of handouts, and (4) determine student perceptions after using handouts in learning. This study uses a 4D development model. The subjects of this study were 10th-grade high school students consisting of small groups (6 students) and large groups (26 students). The results of this study indicate that the validity of the material reaches a percentage of 90% in the